Social Protection of the Poverty: Problems and Solutions - Khairullina, Nursafa Gafurovna; Ustinova, Oksana Vyacheslavovna; Sadykova, Haida Nurgalievna; Tretyakova, Oksana Vladimirovna; Bogdanova, Juliya Zufarovna (International Journal of Economics and Financial Issues, 2016)
The term “social protection of people” is now increasing its popularity both internationally as well as on the national level. This is due to the fact that the transformation processes in the economy and social structure has led to an increase in the number of people needing social protection and support from the state. Today a significant part of Russia’s population is below the poverty line. Despite a steady reduction in the number of people with incomes below the subsistence minimum in Russia in general in most regions this indicator remains high. Socially vulnerable layers of the population such as disabled, pensioners, large families, etc happened to be in particularly difficult conditions. Therefore, the main goal of social protection is to make away with much of the poor population and sometimes miserable existence of the population in an environment where average per capita family income was lower than the level of satisfaction of basic physiological needs. The article presents the results of the survey which diagnosticate the problem and reduce the effectiveness of the social protection system as well as offers the latest trends optimization. Keywords: social protection of people, social work, socially vulnerable groups. JEL Classifications: I30, D14, I38